Midwives and prenatal yoga: An analysis of anowledge and interest in its application - Bara, Farida Tandi; Nopiyanti, Nopiyanti; Nata, Sri Ayu; S, Hartati; Wahdaniyah, Mughni (Institute of Computer Science (IOCS), 2025)
Prenatal yoga is one of the non-pharmacological interventions that has been proven to be useful in supporting the physical and psychological health of pregnant women, as well as preparing for a more comfortable delivery. This study aims to determine the relationship between midwife's knowledge and interest in the application of prenatal yoga in midwifery services in Pangkep Regency. Design an analytical cross-sectional research with a sample of 74 midwives selected through inclusion criteria. Data were collected through an online questionnaire and analyzed univariate and bivariate using Chi-Square test. Most midwives have moderate knowledge (75.7%) and high interest (62.2%), but the application of prenatal yoga is still low (66.2%). There was no significant relationship between knowledge and application (p=0.375), but interest was significantly related (p=0.021). The main barriers include lack of training (70.7%) and absence of instructors (49.3%). Conclusion: Knowledge alone is not enough to encourage the prenatal application of yoga. Increased interest, practical training, and policy support are necessary for effective integration.